Environmental justice in a moment of danger - Sze, Julie (American studies now, 2020)
"We are living in a precarious environmental and political moment. In the US and in the world, environmental injustices have manifested across racial and class divides in devastatingly disproportionate ways. What does the moment of danger mean for the environment and for justice? What can we learn from environmental justice struggles? Environmental Justice in a Moment of Danger examines mobilizations and movements, from protests at Standing Rock to Puerto Rico in the wake of Hurricane Maria. Environmental justice movements fight, survive, love and create in the face of violence that challenges the conditions of life itself. Exploring dispossession, deregulation, privatization, and inequality, this book is the essential primer on environmental justice packed, with cautiously hopeful stories of struggle for the future that we need now"--